2016
DOI: 10.1553/gw-unterricht142/143s49
|View full text |Cite
|
Sign up to set email alerts
|

Bedeutung der politischen Bildung im Geographieunterricht aus der Sicht von Geographielehrkräften

Abstract: Politische Bildung ist ein Unterrichtsprinzip, das interdisziplinär an den deutschen Schulen angewandt wird, um schon hier den Lernenden wichtige Impulse für demokratisches, soziales Denken und Handeln zu geben. Da viele geographische Inhalte politische Zusammenhänge und Diskurse aufweisen, befasst sich dieser Beitrag sowohl mit der Historie dieses Unterrichtsprinzips in der Geographie als auch mit dessen Verständnis durch Geographielehrer/iInnen. Die übergeordnete Fragestellung des Beitrages ist, welche Bedeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 5 publications
1
13
0
2
Order By: Relevance
“…The opinions in relation to the importance are therefore not very far apart, but in relation to the self-assessment of the students or the assessment of the students by their lecturers, this looks different. Regarding skills, the lecturer assessments are very similar to those from various studies that attest to student deficits, especially in the area of argumentation in written work [ 10 , 11 ] as well as in dealing with argumentation and geomedia [ 15 ]. The lecturers also perceived deficits in student writing skills, which were attributed to the way they communicate in digital media.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The opinions in relation to the importance are therefore not very far apart, but in relation to the self-assessment of the students or the assessment of the students by their lecturers, this looks different. Regarding skills, the lecturer assessments are very similar to those from various studies that attest to student deficits, especially in the area of argumentation in written work [ 10 , 11 ] as well as in dealing with argumentation and geomedia [ 15 ]. The lecturers also perceived deficits in student writing skills, which were attributed to the way they communicate in digital media.…”
Section: Discussionmentioning
confidence: 63%
“…This is contrary to a multi-perspective approach, which is necessary in geography lessons. This also applies to geography student teachers, for whom deficits were also identified in this area [ 14 , 15 ]. These deficits are particularly noteworthy because the study by Lytzerinou and Iordanou [ 10 ] showed that the competence of teachers to write argumentations correlates with the ability to assess pupils’ performance in this area.…”
Section: State Of Research/theoretical Backgroundmentioning
confidence: 99%
“…For geography teachers in Germany, various works show that teachers' attitudes to teach ethically open topics and to initiate political judgement is very positive. However, the implementation in the classroom does not take place to the same extent (Applis, 2016;Budke et al, 2016). Many teachers feel overwhelmed by ethical openness.…”
Section: Reflections Of Teachers In Dealing With Sustainability and R...mentioning
confidence: 99%
“…Many teachers feel overwhelmed by ethical openness. Geography teachers sometimes assess their own political knowledge, which is not part of their training, as low (Budke et al, 2016). Laub et al (2021) describe knowledge that would be necessary for ESD II as "subject-related ethical professional knowledge" of teachers and regard it as knowledge that is linked to specialist knowledge.…”
Section: Reflections Of Teachers In Dealing With Sustainability and R...mentioning
confidence: 99%
“…High school students have problems with plausibly connecting information found in literature with a certain cause [74]. Other studies have shown that students successfully work with opinion and justification for these opinions in simple argumentation structures, but struggle with more stages and structures [75][76][77]. Another observation is that, since many issues in geography refer to the everyday lives of students, students tend to have on opinion on issues but commonly have problems justifying this opinion using complex evidence and links with validity [75][76][77].…”
Section: Developing High School Students' Argumentation Skills In Geomentioning
confidence: 99%